Investigation on the Mechanical Characteristics of Sawdust and Chipwood Filled Epoxy - A. P., Puvanasvaran; Sulaiman, Hisham; Sued, Kamil (Penerbit Utem, 2011)
In furniture and paper industries, huge amount of wood flakes and wood flours in the form of chip wood and sawdust are always found as waste. This is known as nature fiber, a renewable source that available at low cost. This study is carried out on the three different size of fiber derived from the chip wood (CW) and sawdust (SW). The particle sizes for CW are based on the grid-opening of sieve that is 150 meshes, 100 meshes and 50 meshes. While sawdust manually shaker are segregated using standard sieve with grid-opening size of 1.0 mm ,0.5 mm and 0.3 mm for small. The SW and CW fiber are blended together with Epoxy respectively using hand tools machine, which is then open molding is employed to form a fiber composite and specimen (fiber composite) accordance to the ASTM standards. It is found that the strength of tensile value for rough size particle of sawdust (SW) is higher than the chip wood (CW). This shows the producing a good quality of SW and CW fibre composite which maybe can use for home furniture utilities.